2016
DOI: 10.4103/0377-4929.191820
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic malignant melanoma of the urinary bladder: A case report and review of the literature

Abstract: Metastatic bladder tumors constitute <5% of all bladder tumors and metastatic malignant melanoma of the urinary bladder is very rare. We present a case report of a metastatic malignant melanoma of the urinary bladder. A 70-year-old woman without any apparent significant clinical history was admitted to the Department of Urology for gross hematuria. Microscopic findings of the transurethral resection specimen revealed fascicles, sheets, and diffuse areas composed of oval and fusiform cells with focal pigmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Metastatic bladder constitutes less than 5% of all bladder tumors and metastatic malignant melanoma to the bladder is very rare with only few cases reported in literature [5]. Clinical evidence of this type of cancer is infrequent and, in most cases, patients presented with hematuria or other urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic bladder constitutes less than 5% of all bladder tumors and metastatic malignant melanoma to the bladder is very rare with only few cases reported in literature [5]. Clinical evidence of this type of cancer is infrequent and, in most cases, patients presented with hematuria or other urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…et al [42] 2011 Primary TURBT and CH some months Efesoy, O. et al [43] 2011 Metastatic TURBT and CHT 7 months Meunier, R. et al [44] 2015 Metastatic TURBT, CH and CHT some months Theocharides, C. et al [45] 2017 Metastatic TURBT and IT some months Paterson, A. et al [46] 2012 Metastatic CH and CHT <5 months Ikeda, A. et al [47] 2013 Metastatic TURBT and CHT <5 months Topal, C.S. et al [48] 2016 Among these, 9 patients had primary/metastatic MM of the kidney and 7 patients primary/metastastic MM of the ureter, 43 patients had primary/metastatic MM of the bladder and 88 patients primary/metastatic MM of the urethra (males and females).…”
Section: Author(s) Year(s) Primary/metastatic Treatment Survivalmentioning
confidence: 99%
“…A few months later, the patient died of metastatic disease progression. Various reports [40][41][42][43][44][45][46][47][48][49][50] have dealt with cases of secondary involvement of the bladder by a previous cutaneous skin melanoma. In one of the most recent of these papers, Topal et al [48] reported their experience of a 70-year-old patient who had presented to the Urology Department for macrohematuria.…”
Section: Urinary Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…Az irodalomban a melanomaáttétekre vonatkozó közlemények leginkább a szisztémás kezeléssel kapcsolatosak [21]. A húgyhólyagot érintő melanomaáttétről 30 esetben számoltak be a szakirodalomban, 8 hónapos medián túlélés mellett [22]. Melanoma áttétét a húgyvezetékben is észlelték néhány esetben.…”
Section: Eredeti Közleményunclassified